BIOGRAFI. AMRAN NUR : WALI KOTA SAWAHLUNTO (2003-2012) - Hermayanti, Hermayanti; Yulia, Refni; Meldawati, Meldawati (Pendidikan Sejarah, 2014)
Struggle of Amran Nur as Mayor of Sawahlunto ( 2003-2012) competent to be traced because Amran Nur assessed have succeeded to bring change of progress of town of Sawahlunto. For that becoming problem formula is 1). How biography of Amran Light 2). How role of Amran Nur in improving progress of town of Sawahlunto and this study aim to to 1). For the mendeskripsikan of picture about biography of Amran Nur 2). For the mendeskripsikan of role of Amran Nur in improving progress of town of Sawahlunto year 2003-2012.Method which is used in this research is history method with the following stages;steps : first,Â  heuristik that is collecting relevant data either through interview study, document, and also book study. Second, criticism of source of that is doing examination of data use criticize eksternal and is internal. Third, data interpretation and analysis. Fourth, historiografi or pour data in the form of erudite article. Result of research indicate that Amran Nur is a leader which is disipilin and strive. Role of Amran Nur in improving progress of town of Sawahlunto among others 1). In the field of education one of the pre-eminent program that is applied Full Day Shcool in the year 2009 with aim to to form character and control the quality of and education of Full applied Day Shcool to be assessed have been able to improve the quality of education in Town of Sawahlunto 2). In the field of health, Amran Nur go into effect program of JPKM subsidized is LOCAL GOVERNMENT equal to 50% 3). In the field of economics, some program of Amran Nur to increase economics of society of Sawahlunto among others : distributing seed- productive seed along with with manure free of charge, giving interest free loan for impecunious family 4). In the field of Infrastructure that is road-works go to production sentra 5). In the field of Tourism, as according to its mission that is making town of Sawahlunto as " town of Wisata Cultured Mine" in year 2010. Which its role is started from development and is hale of old buildings of ommission of Dutch colonial epoch taken as as place of wisata which is memilki assess high history like : Development Of Meseum Train, Hole Mine Mbah Suro, Museum Goedang Ransoem as well as conducting addition of object of wisata among others : Waterboom, Resort Kandi, and others. Pursuant to result of research which have been executed can be concluded that activity of program of Amran Nur during taking hold of as Mayor of Sawahlunto can assess to succeed and that efficacy evidence can be felt by society of Sawahlunto like : Now, Town of Sawahlunto have come to one of the target of place of wisata.Keywords : Biography Of Amran Nur